Productivity shocks and aggregate fluctuations in an estimated endogenous growth model with human capital - Jim Malley; Ulrich Woitek (Center for Economic Studies and ifo Institute (CESifo), 2011)
Employing an endogenous growth model with human capital, this paper explores how productivity shocks in the goods and human capital producing sectors contribute to explaining aggregate fluctuations in output, consumption, investment and hours. Given the importance of accounting for both the dynamics and the trends in the data not captured by the theoretical growth model, we introduce a vector error correction model (VECM) of the measurement errors and estimate the model's posterior density function using Bayesian methods. To contextualize our findings with those in the literature, we also assess whether the endogenous growth model or the standard real business cycle model better explains the observed variation in these aggregates. In addressing these issues we contribute to both the methods of analysis and the ongoing debate regarding the effects of innovations to productivity on macroeconomic activity.
Keywords: C11; C52; E32; 330; endogenous growth; human capital; real business cycles; VECM measurement errors; Bayesian estimation